Advanced In-Situ Instrumentation of RF Circuits for Mixed-Field Irradiation Testing Purpose - Müller, Steffen; Danzeca, Salvatore; Garcia Alía, Rubén; Brugger, Markus; Weigel, Robert; Kölpin, Alexander (European Conference on Radiation and its Effects on Components and Systems (RADECS), 2017)

A High Performance Line Filter for Narrowband Power Line Communication Testbed Applications - Müller, Steffen; Lurz, Fabian; Weigel, Robert; Kölpin, Alexander (IEEE International Conference on Smart Grid Communications (SmartGridComm), 2013)
This paper is presenting a two-stage line filter design, optimized for power line communication (PLC) testbed applications in the frequency range from 9 kHz to 500 kHz. The filter shows a very high differential mode attenuation together with a high input impedance on load-side. It enables to cope with the harsh noise characteristics of the PLC channel, as well as varying line access impedances in order to build up testbeds without any additional equipment. After exploring the filter’s architecture, SPICE simulations and measurement results are carried out, while the latter are discussed with respect to two commercial off-the-shelf filters.
elib2cris::1512001600,mueller2013
Keywords: Power Line Communication; Smart Grid; Line Filter; Electromagnetic Interference; Testbed

A Survey on Analog-to-Digital Converter Performance with Respect to Ionizing Radiation - Müller, Steffen; Weigel, Robert; Kölpin, Alexander (European Conference on Radiation and Its Effects on Components and Systems (RADECS), 2017)

Challenges on COTS-based Radiation Tolerant Communication System Design - Müller, Steffen; Kölpin, Alexander (DLR Bauteilekonferenz, 2017)

Circuit Design for a Radiation Tolerant 2.4 GHz Synthesizer Based on COTS Components - Müller, Steffen; Danzeca, Salvatore; Garcia Alía, Rubén; Brugger, Markus; Weigel, Robert; Kölpin, Alexander (IEEE Topical Workshop on Internet of Space (TWIOS), 2018)

In-Containment Signal Conditioning and Transmission via Power Lines within High Dose Rate Areas of Nuclear Power Plants - Müller, Steffen; Dennerlein, Jürgen; Janke, Iryna; Weber, Johannes; Weigel, Robert; Kölpin, Alexander (4th International Conference on Advancements in Nuclear Instrumentation Measurement Methods and their Applications (ANIMMA), 2015)
Signal conditioning and transmission for sensor systems and networks within the containment of nuclear power plants (NPPs) still poses a challenge to engineers, particularly in the case of equipment upgrades for existing plants, temporary measurements, decommissioning of plants, but also for new builds. This paper presents an innovative method for efficient and cost-effective instrumentation within high dose rate areas inside the containment. A transmitter-receiver topology is proposed that allows simultaneous, unidirectional point-to-point transmission of multiple sensor signals by superimposing them on existing AC or DC power supply cables using power line communication (PLC) technology. Thereby the need for costly installation of additional cables and containment penetrations is eliminated. Based on commercial off-the-shelf (COTS) electronic parts, a radiation hard transmitter is designed to operate in harsh environment within the containment during full plant operation. Hardware modularity of the transmitter allows application specific tradeoffs between redundancy and channel bandwidth. At receiver side in non-radiated areas, signals are extracted from the power line, demodulated, and provided either in analog or digital output format. Laboratory qualification tests and field test results within a boiling water reactor (BWR) are validating the proof of concept of the proposed system.
elib2cris::1512001600,mueller2015a
Keywords: Power Line Communication; PLC; radiation hard electronics; radhard; sensor networks; online monitoring; OLM; monitoring and diagnostics; M&D

In-Situ Testing of a Multi-Band Software-Defined Radio Platform in a Mixed-Field Irradiation Environment - Budroweit, Jan; Müller, Steffen; Jaksch, Matthis; Garcia Alía, Rubén; Coronetti, Andrea; Kölpin, Alexander (Aerospace, 2019)
This paper presents an in-situ test concept for a multi-band software-defined radio (SDR) platform in a mixed-field radiation environment. Special focus is given to the complex automated test setup with respect to the requirements of the irradiation facility. Additionally, selected test results of a system-level evaluation are presented and discussed. For the verification of the mixed-field radiation environment, the software-defined radio (SDR) was also tested under proton irradiation. The cross-sections for the observed single event eects are compared and show similar results.<br
Keywords: in-situ testing; automated test setup; mixed-field irradiation; total dose effects; single event effects; software-defined radio